Pengembangan Kurikulum PAI Di Sekolah Umum - Yunita, Yuyun (Jurnal Dewantara, 2016)
National Education Act, there are 4 chapters and 10 verses that speak about the curriculum, namely: Article 36, paragraph 3, namely: curriculum prepared in accordance with the level of education within the framework of the Unitary Republic of Indonesia with respect to: Increasing Faith and Piety; Increased Noble Morals; Increased potency, Intelligence, and Interests of Students; Regional Potential Diversity and the Environment; And the demands of the National Regional Development; The demands of the workplace; The development of Science, Technology, and Art; Religion; Dynamics of Global Development; And the National Unity and Values ​​Nationality. National Education serves to develop the ability and character development and civilization of the nation's dignity in the context of the intellectual life of the nation, is aimed at developing students' potentials to become a man of faith and devoted to God Almighty, noble, healthy, knowledgeable, skilled, creative, independent and become citizens of a democratic and responsible, one through the Islamic Religious Education.